Glucose homeostasis after simultaneous pancreas and kidney transplantation: a comparison of subjects with C‐peptide‐positive non‐type 1 diabetes mellitus and type 1 diabetes mellitus. Issue 1 (26th November 2015) - Chakkera, Harini A.; Kudva, Yogish C.; Chang, Yu‐Hui H.; Heilman, Raymond L.; Singer, Andrew L.; Mathur, Amit K.; Hewitt, Winston R.; Khamash, Hasan A.; Huskey, Janna L.; Katariya, Nitin N.; Moss, Adyr A.; Behmen, Senaida; et al.
Abstract: Background: While simultaneous pancreas kidney transplant (SPKTx) is a therapeutic option for patients with type 1 diabetes (T1DM) and renal failure, few centers offer SPKTx to "select" non‐T1DM patients. To address concerns that existing insulin resistance may limit the benefits of the pancreas allograft among non‐T1DM, we compared several indices of glucose homeostasis, in "select" non‐T1DM and T1DM patients who received SPKTx. Methods: Criteria for "select" non‐T1DM included the following: positive C‐peptide, BMI <30 kg/m 2, treatment with oral agents before insulin initiation, and insulin at <1 unit/kg/d. We compared several indices of glucose homeostasis within 1 yr post‐SPKTx among seven "select" patients with non‐T1DM and nine patients with T1DM with similar age, BMI, and immunosuppression. Measurements of insulin resistance included the following: homeostatic model, insulin sensitivity index, and insulin–glucose ratio; insulin secretion measures included the following: corrected insulin response. Results: Non‐T1DM had similar pre‐transplant metabolic (fasting glucose, HbA1c, blood pressure, and lipid) parameters to the T1DM cohort. There were no significant differences in the various measures of insulin resistance and secretion between T1DM and "select" non‐T1DM patients. Conclusion: Our results suggest SPKTx should be considered in the therapeutic armamentarium among carefully select non‐T1DM with features of minimal insulin resistance; however, a larger cohort with longer follow‐up is needed to confirm our results.